Tail Oil - a Raw Material of Promise for India - Mukebji, A. K. (Indian Forester, 1979)
Paper reviews the advancement made by the Toil oil industry in the world. It also briefly describes the process of its reeovery and fractionation for yielding important products of industrial and commercial value. An assessment of the current available sources of Tail oil and its potential future availability in India, for the development of such an industry, has also been given. The present loss to the Indian Paper Mills, due to non recovery of Tail oil from the b1aek liquor, has been qualified. A suggestion has been made for its immediate recovery and and use in various local industries. The estimated cost of recovery of Tail oil and its fractionation alongwith cost of know-how and imported machinery have been indicated. It is felt that this industry can have a very bright future in India.